A területfejlesztés fogalmáról - Faragó, László (Tér és Társadalom, 1987)
We all suffer from the lack of an established, unified terminology and of a general agreement on the basic categories in the discipline concerned with regional questions (Regional Science?). The author puts forward an interpretation of the concept development hoping to contribute to the elucidation of some problems in this field. He introduces the concept of regional development intuitively, with the help of some general principles, defining it as a policy and its realizing mechanism which is meant to increase efficiency in the process of social reproduction (production – distribution – exchange – consumption) by influencing the spatial existence of society. In a narrow meaning this includes the theoretical (ideological) and acitivity system which – in full knowledge of spatial relationships – to change the existing spatial conditions for presumed or real benefits. In a broader meaning regional development also includes the means used for realizing this policy and the objects it creates since the latter cause irreversible changes in space for a shorter or longer period of time. Consciousness is a specific difference in such a way that it counts not only on accidental and spontaneous phenomena but makes use of the already functioning automatisms as well. After these considerations the author places the concept of regional development in the system of cognate ideas, distinguishing it from the development of settlement networks and larger areas, or, better to say, unites them all in the same concept. The content of the concept is detailed in a description of the general tasks, main objectives, agents and means of regional development. In conclusion the author mentions some issues presumed to gain importance in the (near) future which, at the same time, represent important tasks for scientific research. By striving to extend the concept of regional development beyond the generally accepted scope the author intends to provide a broader basis for the analysis of regional political issues. His views can be questioned or accepted – in either way reactions can contribute to better theoretical or practical results.